دور الإذاعة المحلية في غرس القيم التعليمية - جديدي, سيرين; لعويني, سلسبيل (جامعة الوادي - University of Eloued, 2023)
عالجت هذه الدراسة إشكالية مدى مساهمة الإذاعة المحلية للوادي و المغير في غرس القيم التعليمية من خلال برنامج أهلا لقرآن , و تمحورت إشكالية الدراسة كالتالي : ما هو دور الإذاعة المحلية في غرس القيم التعليمية من خلال برنامج " أهل القرآن " بإذاعة الوادي و المغير؟ و اختيارنا لهذا الموضوع كان بسبب إهتمامنا الخاصبالعملالإذاعيباعتباره يندرج ضمن مجال تخصصنا وكذلك لقلة الأبحاث التي ترتكز على تجارب الإعلام التعليمي , كما تحتل هذه الدراسة أهمية كبيرة كونها تبرز الدور الذي تلعبه الإذاعة المحلية في نشر القيم التعليمية ,هذا و تم إجراء هذه الدراسة بالاعتماد على المنهج المسحي على عينة قصدية , و ذلك عن طريق الاعتماد على أداتي المقابلة في الجانب النظري و الاستبيان في الدراسة الميدانية , و هذه الأخيرة تم تطبيقها على عينة قصدية من مستمعي برنامج أهل القرآن بولاية الوادي , و قد توصلت الدراسة إلى مجموعة من النتائج أهمها ما يلي : - كشفت الدراسة بأن للمستوى التعليمي دور في متابعة برنامج أهل القرآن . - كشفت ا لدراسةبأن برنامج أهل القرآن يساعد على ربط المعلومات النظرية بالجانب التطبيقي . - كشفت الدراسة أن السبب الرئيس من متابعة برنامج أهل القران هو لتعلم أحكام القراءة. - كشفت الدراسة أن برنامج أهل القران نجح في نشر القيم التعليمية. Our objective in this study is to measure the extent to which the local radio of the valley and the changer contributed to the inculcation of educational values through the Quranic People's Program. The problem of the study was as follows: What is the role of local radio in instilling educational values through the programme "The People of the Koran"? Our choice for this topic was due to our particular interest in radio work as it falls within our field of specialization as well as to the lack of research based on educational media experiences. This study is also of great importance as it highlights the role played by local radio in the dissemination of educational values. This study was conducted based on the survey curriculum on an intentional sample. And that's by relying on my corresponding tools in the theoretical aspect and questionnaire in the field study, The latter was applied to a deliberate sample of the listeners of the Quran People's Program in Eloued State. The study found a series of results, the most important of which are: The study revealed that the educational level has a role in following up the People of the Qur’an program. The study revealed that the People of the Qur'an program helps to link theoretical information with the practical side. Daily time spent listening to local radio is less than half an hour. The study showed that most members of the community follow the valley's local radio programmes and sometimes the changer. -Religious programs top the list of preferred programs of sample individuals. -The study revealed that most individuals like the Quran People Program. -The study revealed that the main reason for pursuing the Peers programme is to learn the reading provisions. -The Qur 'an program helps to link theoretical information to the applied aspect. -The "People of the Koran" program helps learn the provisions of intonation by elders. -The "People of the Koran" programme helped to highlight the competence of the learner. -The "People of the Koran" programme contributed to the teaching of the Koran's recitation with a workshop novel about Nafa. -The Quran People's Program successfully disseminated educational values.
مذكرة ماستر إعلام وإتصال
Keywords: دور , الإذاعة المحلية , غرس , القيم التعليمية; role, local radio, instilling, educational values